Random mutagenesis of the human immunodeficiency virus type-1 trans-activator of transcription (HIV-1 Tat). - Siderovski, D P (1992)
A new method is described for the direct construction of randomly mutagenized genes by applying the polymerase chain reaction (PCR) to an oligonucleotide synthesized using doped nucleotide reservoirs. We have demonstrated the utility of this method by generating a library of mutant HIV-1 tat genes. Several arbitrarily selected, inactive tat clones were sequenced to evaluate the extent of the mutagenesis. Moreover, fourteen recombinants encoding varying levels of transcriptional trans-activator activity were isolated by transient transfection of sub-library pools into a HeLa cell line bearing an HIV-LTR-chloramphenicol acetyltransferase (CAT) reporter gene. Sequence data revealed a spectrum of alterations including nucleotide substitutions, insertions, and deletions, suggesting that mutations arose from both the doped DNA synthesis and the subsequent PCR 'rescue' of full-length product. Sequence comparison between inactive and active Tat clones revealed a selection pressure against amino-acid substitutions within the N-terminal domains of Tat, indicating the importance of this region to trans-activation competence. In addition, single and double missense mutations within the basic-rich, TAR RNA-binding domain were seen to be tolerated within active Tat clones.